Gaza War: Preliminary Findings on the Socio-Economic and Environmental Impact on Lebanon - United Nations Development Programme (United Nations, 2023)
The outbreak of the war in Gaza on has resulted in an additional layer of complexity to the already profound and multifaceted crisis that Lebanon has been struggling with for the past few years. The impact has started to be felt across sectors, and through a variety of transmission channels. The ongoing conflict around the Southern Lebanese border that has been triggered by the war is expected to have significant impact on key economic sectors in Lebanon, particularly tourism and services. The economy of South Lebanon has been and will be affected, given the direct military attacks targeting a high number of southern villages and towns, the high displacement rates, and the reported shutdown of economic activity. This UNDP report, launched December 19, 2023, is an early attempt to take stock of losses and inflicted damages to provide evidence for the implementation of the triple nexus and thus complementing humanitarian assistance with developmental support, and to provide an unbiased baseline to guide future programmatic responses of UNDP and partners for recovery, reconstruction and stabilization.